Türk Hukukunda bankaların sır saklama yükümlülüğü - Kandıralıoğlu, Pınar Çağla (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Hukuk Anabilim Dalı / Özel Hukuk Bilim Dalı, 2010)
Banka ve müşteri arasındaki iş ilişkisi banka sırrının kaynağıdır. Banka ve müşteri arasında oluşan güven ilişkisi sır saklama yükümünün gerekçesidir. Bankalar, iş ilişkisi çerçevesinde, müşterilerine ait her türlü bilgi ve rapora sahip olurlar. Bu sebeple, bankalara, müşterilerine ve müşteri çevresine ait sırları saklama görevi kanunnen getirilmiş bir yükümlülüktür. 5411 sayılı Bankacılık Kanunu m. 73'de; sırların saklanması başlığı altında, "bankaya ve müşteriye ait sır" ifadesi kullanılmaktadır. Müşteriye ait sırlar meslek sırrı kapsamında değerlendirlmektedir. Müşterinin menfaatinin olduğu tüm konuları kapsamaktadır. Müşteri sırrını saklamakla yükümlü kişiler arasında banka tüzel kişiliği, organları ve çalışanları sayılmaktadır. Bu hüküm özel hukuk karakteri ile birliktecezai karakterde taşımaktadır. Müşteriye ait sırların açıklanabilmesinin yasal sınırları Bankacılık Kanunu ile belirlenmektedir. Yasal sınırlar kapsamında bilgi açıklanması halinde bankanın sorumluluğu söz konusu olmayacaktır.
The obligation of secrecy in Turkish Bank Law
The internal or private relationship between the banks and their customer is the source of banking confidentiality. In the framework of this internal relationship the banks acquire all types of information and reports. Therefore keeping the information relating to either customers or circle of customers secret is an obligation for the banks promulgated by law. The confidence between the banks and their customers is the base and justification of the banks? responsibility relating to the keeping the information secret. Article 73 of Banking Law No. 5411 which was drafted in accordance with the the EU directives, under the title of confidential matter, the concept of banks and customers secrecy is used. The customers secrecy must be considered as professional secret or trade secret, and it is also extended to all matters in which the customers have benefit. The authorities and staff of the bank are accounted as among those who have to keep customers? information secret. The provision of the Banking Law has not only civil and commercial law character but also a criminal. The legal limits for making public of the secret information belong to the customers are drawn by the Banking Law. No liability arises for the banks in situations where the secret information of customers is made public in accordance with the limits determined by law.
Keywords: Banka Hukuku; Banking Law; Banka çalışanları; Bank employees; Bankacılık; Banking